Inhibition of Mico.nazole --resistant mutants o'f Candida al:J,lcalts; by aqueous extract of Matric aria chamomile - Mohammed, B.M.; Ali, B.. Z.; Naef, R. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
fhe  .rudy has shad a light on the abi_ lity Qf  aq,ueous. extract ofMairlr:aria chamomile ibr eliminating growth of miconazole. .resistantmuta.nt of Candida   albkÂ·afzy. whi-ch  i:,solated  from . human. ruiil and vagina ;Tfl- inimJ.tJTI  inhibition  cohc!:lhtra_tion  (MIC) is l6 Jrl'g/n: l. Spon-taneous tesistant  .mutatiqns-.fot mic-onazole were also is:ola ed by using sp 1-f.g/ml of rni:comlzoJeThis   ::onc ntrf}:ti:o:n  is five times more than   the  MIC .Different c